Penguatan Kesadaran Anti-Bullying melalui Implementasi Layanan Bimbingan dan Konseling di Sekolah Dasar Desa Pasilian 01 - Alya Fatiha; Putri Nurina; Aceng Akhmad Munanzdar Alkafi Billah Billah; Desi Setiyadi; Dina Panisa; Kamilatusolihah Kamilatusolihah (Fakultas Tarbiyah dan Keguruan, 2026)
Bullying remains a prevalent issue in elementary school environments and has negative impacts on students’ social-emotional development, academic achievement, and psychological well-being. Based on the needs assessment conducted at SDN Pasilian 01, aggressive behavior among students was still identified, which was influenced by limited understanding of the impacts of bullying and the lack of optimal prevention and intervention strategies implemented by the school. This community service program aimed to implement guidance and counseling services through the Stop Bullying Program to enhance anti-bullying awareness, social skills, and the creation of a safe and inclusive school environment. The program was carried out using a participatory approach through socialization activities, group guidance and counseling services, student mentoring, and collaboration with teachers and parents. Program evaluation was conducted through observations, interviews, and documentation throughout the implementation process. The results indicated an improvement in students’ understanding of bullying, increased participation in anti-bullying discussions, and the development of mutual respect in daily interactions. Furthermore, the program strengthened the collaboration between the school and parents in supporting sustainable bullying prevention efforts. Therefore, the implementation of guidance and counseling services through the Stop Bullying Program can serve as an effective strategy for fostering a safe, supportive, and child-friendly school culture that promotes students’ overall development.